Genetic variability and selective breeding for traits of aquacultural interest in the Pacific oyster (Crassostrea gigas) - Boudry, Pierre; Degremont, Lionel; Taris, Nicolas; Mccombie, Helen; Haffray, Pierrick; Ernande, Bruno (Aquaculture Association of Canada, 2004)
The most significant genetic improvement for production of Pacific oyster (Crassastrea gigas) has been obtained through the breeding of triploids, especially since the development of tetraploids. Quantitative genetics studies suggest that significant gains, for disease resistance or for other traits of aquacultural interest, could be obtained using this approach. However, the limited extent of hatchery-propagation (versus natural recruitment) and/or various technical difficulties and biological characteristics of the species have slowed the development of selective breeding programs. Recently, in the USA, Australia and New Zealand, family-based selective breeding programs have been initiated to improve growth and yield. In Europe, where both natural and hatchery propagated spat are farmed, no large-scale selective breeding programs have been initiated. However, special attention has been paid to "summer mortalities", for which the causal factors are still unclear. Our studies have shown that family-based selective breeding can improve spat survival, with no impact on growth. However, a genetic (rade-off between survival and reproductive allocation was shown il1 adults, but was influenced by environmental variation. This might explain how additive genetic variance for fitness-related traits is maintained in wild populations. Practical difficulties in breeding large numbers of families are a major constraint for family-based selective breeding in oysters. Genetic variability exists for several larval traits, which increases the imbalance in reproductive success between breeders in hatchery-propagated populations. Multiplexed-microsatellite markers can be efficiently used to trace parentage in mixed-fami1y breeding programs. Finally, a new means of introgression of traits of interest from genetically improved diploids to polyploids will allow the combination of selective breeding and polyploidization